Pengaruh Gaya Kepemimpinan Dan Tingkat Kedisiplinan Kerja Terhadap Kinerja Karyawan Di Unit PT.Bank BTPN Syari'ah,TBK Cabang Serang - Listiawati; Angrian Permana; Isma Khoirunnisa (Jurnal Ekonomi, 2017)
The purpose of this study is to examine the influence of leadership style and the level of discipline on the performance of employees in the Unit PT.Bank BTPN Syari'ah, TBK Serang Branch. The research method used is quantitative by using the descriptive approach method with the questionnaire as a research instrument. Simultaneously there is an influence between Leadership Style and Discipline on employee performance. value of correlation coefficient between leadership style and discipline to employee performance of 0.908 (very strong). the value of determination coefficient of 0.824, meaning leadership style (x1) and discipline (x2) contributed 82.4% to employee performanceÂ (Y), while the remaining 17.6% influenced other variables not described in this study